A preliminary study on operation management for one-way EV car sharing system in university campus - Katamine, Keiichi; Umeda, M.; Ueno, K.; Hashim, Shaiful Jahari; Syed Mohamed, Syed Abdul Rahman Al-Haddad; Abdullah, Rusli; Sharif, Khaironi Yatim (2017)
Car sharing using electric vehicles(EVs) is effective in local society and community from the viewpoint of economy and the protection of the natural environment. For instance, Univerisiti Putra Malaysia (UPM), which has two large campuses, has a plan to use a small number of small EVs as one of transportation methods. When a large number of people share a small number of vehicles in this way, the confliction of usage requests by users may cause inconvenience to users and ineffective operation of vehicles. In addition, because the degree of legal compliance with usage time and operation rules relies on social and cultural backgrounds, operation methods may be affected by them. Therefore, a framework for supporting operation management in consideration of characteristics of the local society and community is necessary in order to efficiently operate a limited number of vehicles without detracting from the convenience of users. We have been developing an operation management support system for one-way EV car sharing in the university campus to improve user convenience and vehicle operation efficiency. In this presentation, we clarify the issues of operation management for car sharing system. We also introduce an overview of the operation management support system and propose several reservation methods of vehicles.